Geologi dan Studi Cleat Terhadap Kualitas Batubara Pada Daerah Air Panas, Kecamatan Loa Janan, Kabupaten Kutai Kartanegara, Provinsi Kalimantan Timur - Arya, Melia Fajri Sukma; Rahmad, RM. Basuki (Jurnal Ilmiah Geologi PANGEA, 2024)
The research location is in Air Panas Area, Loa Janan Subdistrict, Kutai Kartanegara Regency, East Kalimantan Province and is included in the Kutai Basin with coal-bearing formation which is Balikpapan Formation. This study aims to determine the local geological conditions in the study area and the influence of cleat on coal quality. The research stages include literature study, geological mapping, and cleat data collection. The analysis was conducted in the form of flow pattern analysis, landform analysis, petrographic analysis, geological structure analysis, micropaleontology analysis, depositional environment analysis, and cleat analysis on coal quality. The analysis shows that the study area has radial and sub-trellis flow patterns. Geomorphological conditions consist of mining landforms, mine ponds/sumps, dumps, river bodies, swamps, flood plains, structural hills, and remnant hills. The stratigraphy of the study area from old to young is composed by Balikpapan mudstone unit, Balikpapan sandstone unit and alluvial deposits. Based on the measured stratigraphic cross section, the depositional environment is Transitional Lower Delta Plain. The developed geological structure is formed due to the main thrust that has Southeast-Northwest direction that produces bridle, cleat, and fold structures. Cleat characteristics in the study area show a normal pattern and are not affected by geological processes in the form of geological structures (endogenic cleat). Special study studies show that cleat attribute data in the form of cleat length, cleat spacing, and cleat openings can affect the quality of coal seams, especially on ash, total sulfur, and calorific value.